31.6k views
1 vote
(x-1)^2+(2-x)^2-3(x-5)*(x-5)

User Paaacman
by
6.0k points

1 Answer

4 votes

Answer:


-x^2+24x-70

Explanation:


(x-1)^2+(2-x)^2-3(x-5)*(x-5)\\=> (x - 1)^2 + (2 - x)^2 - 3(x - 5)^2\\=> x^2 - 2x + 1 + 4 - 4x + x^2 - 3(x - 5)^2\\=> x^2 - 2x + 5 - 4x + x^2 - 3(x - 5)^2\\=> x^2 - 6x + 5 + x^2 - 3(x - 5)^2\\=> 2x^2 - 6x+5 - 3(x - 5)^2\\=> 2x^2 - 6x+5 - 3(x^2 - 10x + 25)\\=> 2x^2 - 6x+5 - 3x^2+30x-75\\=> -x^2 - 6x + 5 + 30x - 75\\=> -x^2 + 24x + 5-75\\=> -x^2+24x-70

Formula used =


(a-b)^2 = a^2+ 2ab + b^2

User Nomoa
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.